GASTROPARESIS; AN UNUSUAL INDICATION FOR GASTRECTOMY - Ahmet Gökhan TÜRKÇAPAR; H. ÇETİNKAYA and Kubilay ÇINAR and Rıfkı HAZIROĞLU and Ergun ERDEM and Kadir BAHAR and A. ÖZDEN and Ercüment KUTERDEM (Turkish Journal of Gastroenterology, 2020)
-